Short-term acute constipation and not short-term acute diarrhea altered cardiovascular variables in male Wistar rats (Nigerian Journal of Physiological Sciences, 2022)
Gastrointestinal dysmotility is a substantial public health challenge globally. Based on previous findings in developed countries, it has been observed that there is an association between diarrhea, constipation, and some cardiovascular variables. This study investigated the effects of experimentally-induced short-term acute constipation and short-term acute diarrhea on certain cardiovascular variables in rats. Thirty (30) male Wistar rats (150 -180 g) were divided into three groups; Control, Diarrhoea, and Constipation. The experiment was carried out in 2 phases, the period after induction and the recovery period, and 5 animals per group were used for each phase. The control group received an equivalent amount of distilled water while Diarrhoea and the Constipation group were induced by oral administration of 2ml Castor oil and administration of Loperamide (3mg/kg, b.d, orally x 3 days), respectively. Cardiovascular variables were assessed using the Edan Scientific® Electrocardiography and  Heart Rate Variability machine. Recovery was allowed for 4 days after the onset of the procedure and cardiovascular parameters were reassessed. Post-induction Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP) and Heart Rate (HR) significantly increased in constipated rats (153.2 ± 2.9 mmHg; 109.0 ± 3.7 mmHg;     123.7 ± 3.2 mmHg; 123.4±5.6 bpm) when compared with the control values (95.5±4.8 mmHg; 61.2 ± 3.5 mmHg; 72.6 ± 3.6 mmHg; 72.3 ± 5.2 bpm), respectively. The recovery SBP, DBP, MAP, and Heart Rate in the constipated group remained significantly higher compared to the control. Diarrhea had no significant effect on the parameters determined in both post-induction and recovery phases. The electrical activities did not change in both experimental groups compared to the control. This study revealed increased SBP, DBP, MAP, and HR in short-term acute constipated rats but not so with short-term acute experimental diarrhea